Hématomes Extraduraux Chez L’adulte Au Togo - Beketi, Katanga Anthony; James, Edem Yaovi; Gnadi-Piou, Faré; Kpelao, Essossinam; Tagba, Pazimassouwé; Moumouni, Abdel-kader; Ahanogbé, K. M Hobli; Walla, Atchi; Dossim, Assang Michel (European Scientific Journal, ESJ, 2018)
Purpose: The purpose of this work was to evaluate our neurosurgical practice about extradural hematoma and to describe their prognosis in our context. Patients and methods: This is a retrospective study of patients treated for extradural hematoma at Sylvanus Olympio university teaching hospital, which houses the only neurosurgery unit in Togo between April 2008 and August 2014. We included in our study, the files of patients of both sexes, aged over 15 years, with extradural hematoma isolated or not at the cerebral scanner, treated during the study period. Thus, 62 patients were taken into account. There was a male predominance (sex ratio of 19.7). The average age was 29.8 years with extremes of 02 and 70 years of which 41.9% of patients were between 20 and 29 years old. The surgical technique was the making of a burr hole or a cranial flap. We examined the parameters related to surgical treatment and the evolutionary mode. Results: In this study, 34 patients (54.8%) underwent surgery: cranial section (27 cases), widened hole craniotomy (07 cases). The average time between trauma and surgery was 09 days with extremes of 01 to 30 days. Twenty-four patients were operated more than 48 hours after diagnosis and the average postoperative follow-up time was 11.1 days with extremes of 07 and 18 days. Twenty-eight patients (45.2%) were not operated on. Among them, 20 patients presented with a HED blade (thickness of less than 10mm) and the eight (08) others for lack of financial means. The average hospital follow-up time for non-operated patients was 15.4 days with extremes of 08 and 60 days. The evolution was evaluated by the Glasgow Outcome Scale over three months. Fifty-five patients or 88.7% recovered without sequel. We obtained 3 cases (4.8%) of deaths including 2 cases that were not operated due to lack of financial means. Conclusion: We have observed that a low Glasgow admission score, long treatment delays, and associated lesions are factors that appear to reduce the prognosis in the treatment of extradural hematoma in Togo. These prognostic factors must be better documented in our future studies to identify them in order to act on them in order to reduce the morbidity and mortality that these extra-mural hematoma cause in our environments.